Study of behavioral intention: A mediator for behavioral use in the hospital industry - Hamdi, Edi; Anggraeni (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2025)
The health industry sector, specifically hospitals, is an important industrial sector because it is related to providing high-quality health services and care to citizens in every country in the world. One way to improve health services in hospitals is to improve information technology (IT) applications in hospitals. This research aims to analyze the influence of performance expectancy, effort expectancy, social influence, and facilitating conditions on behavioral intention and analyze whether the behavioral intention is needed as mediation for use behavior and its impact on use behavior in hospital information systems. The population of this study was health workers who worked at Mitra Keluarga Hospital in the Jabodetabek area with a total of 4755 samplings using the Slovin formula, resulting in 368 samples. In this research, hypothesis testing uses the Structural Equation Model-LISREL analysis technique. The results of this study confirm that performance expectancy has a significant effect on behavioral intention. However, the effort expectancy and social influence variables show no effect on behavioral intention. Then facilitating conditions and behavior intention have a significant effect on use behavior.